1999
DOI: 10.3143/geriatrics.36.420
|View full text |Cite
|
Sign up to set email alerts
|

An Autopsy Case of Pulmonary Embolism Due to Renal Angiomyolipoma in an Elderly Woman.

Abstract: An 86-year-old woman with a 13-year history of hypertension was admitted because of consciousness disturbance, hypotension, tachycardia, and cyanosis at her extremities. Enhanced computed tomography showed a thrombus in the truncus pulmonalis and right pulmonary artery, and also showed a left renal mass and a right renal cyst. Under a diagnosis of pulmonary embolism we started anticoagulant therapy, but the patient died five days after admission. At autopsy, a saddle-like thrombus was found in the truncus pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…More severe presentations were right-sided heart failure in a patient whose thrombus totally occluded the IVC [11] and hypotension in a patient with intratumoral hemorrhage found later on pathology [34]. Shinohara et al reported a case that presented with signs of massive PE and cardiogenic shock (hypotension, tachycardia, and cyanosis); no thrombus was found anywhere in the venous circulation of the patient except in the truncus pulmonaris and the two pulmonary arteries.…”
Section: Angiomyolipoma With Inferior Vena Cava Invasionmentioning
confidence: 99%
“…More severe presentations were right-sided heart failure in a patient whose thrombus totally occluded the IVC [11] and hypotension in a patient with intratumoral hemorrhage found later on pathology [34]. Shinohara et al reported a case that presented with signs of massive PE and cardiogenic shock (hypotension, tachycardia, and cyanosis); no thrombus was found anywhere in the venous circulation of the patient except in the truncus pulmonaris and the two pulmonary arteries.…”
Section: Angiomyolipoma With Inferior Vena Cava Invasionmentioning
confidence: 99%
“…Several cases of pulmonary thrombosis have been reported in patients with AML with venous extension 5 , 6 , 7 ) . A few patients were asymptomatic; however, 1 death was reported 8 ) . Turowski reported a case of a 20-year-old patient who developed cardiac arrest secondary to pulmonary embolism during nephrectomy 6 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Case reported by Shinohara et al presented with congestive heart failure with a thrombus extended to the right atrium [57]. …”
Section: Discussionmentioning
confidence: 99%